The social doctrine and presence of the Catholic Church in the media - Balabanić, Ivan, sociolog (Array, 2020)
The social doctrine of the Church involves greater commitment and engagement of the Church in social problems as well as the promotion of relationships that serve justice and peace. The Catholic Church first began relating mass media to its social teaching in the 19th century. As the Church aimed at a broader scope of public, it dealt with means of social communication and examined it through numerous sources – papal encyclicals, conciliar and episcopal documents. The relationship between the Catholic Church and the media is not simple. Approaches to ethics, morality, responsibility and dignity of human beings are sometimes different in media reports and in the aims of the Church in its social doctrine which should provide all members of the society with a sense of direction and instruction for everyday actions. Through the documents presented here, the Church has shown a readiness to face the media as well as the possibility to use them for advancing justice, truth, peace and freedom.